Stress in the Educational System as a Potential Source of Epigenetic Influences on Children's Development and Behavior - Frías-Lasserre, Daniel; Villagra, Cristian A.; Guerrero-Bosagna, Carlos (Frontiers in Behavioral Neuroscience, 2018)
Despite current advances on the relevance of environmental cues and epigenetic mechanisms on biological processes including behavior, little attention has been paid to the potential link between epigenetic influences and the educational sciences. For instance, could the learning environment and stress determine epigenetic marking, affecting student behavior development?. Could this have consequences on educational outcomes? So far, it has been shown that environmental stress influences neurological processes and behavior both in humans and rats. Through epigenetic mechanisms, offspring from stressed individuals develop altered behavior without any exposure to traumatizing experiences. Methylated DNA and noncoding RNAs regulate neurological processes such as synaptic plasticity and brain cortex development in children. The malfunctioning of these processes is associated with several neurological disorders, and these findings open up new avenues in the design of benign epigenetic environments for education and therapy. In this article, we discuss current cases of stress and behavioral disorders found in youngsters, and highlight the importance of considering epigenetic processes affecting the development of cognitive abilities and learning within the educational environment and teaching methodologies.